2023
DOI: 10.3390/ma17010004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Tensile Performance of FRP Tendons/Cables with Varied Bond Anchorage Factors

Xing Zhao,
Lanjinhua Meng,
Sihao Li

Abstract: FRP tendons and cables are increasingly being used in civil engineering structures due to their high strength-to-weight ratio and corrosion resistance. The bond anchorage factors, which characterize the bond strength between the FRP tendon/cable and the surrounding materials, play a critical role in determining the overall performance of the system. In this study, a series of tensile tests were conducted on FRP tendons/cables with different bond anchorage factors to evaluate their load-carrying capacity, load–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The inclusion of hoop reinforcement should be considered in structural design, especially when dealing with larger diameter rebars or when controlling radial crack formation. From Figure 11, it can be observed that the AAE for bond strength predicted by Equation ( 7) is 1.21 with a STD of 0.39, whereas for Equation ( 8), the AAE is 0.99 with an STD of 0.29, indicating that the calculations from Equation (7) tend to overestimate the experimental values, while Equation (8) shows better predictive accuracy. This is attributed to the similar surface properties of SFCB and FRP reinforcement, as well as the similarity in bond failure mechanisms between SFCB-concrete and FRP-concrete.…”
Section: Design Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of hoop reinforcement should be considered in structural design, especially when dealing with larger diameter rebars or when controlling radial crack formation. From Figure 11, it can be observed that the AAE for bond strength predicted by Equation ( 7) is 1.21 with a STD of 0.39, whereas for Equation ( 8), the AAE is 0.99 with an STD of 0.29, indicating that the calculations from Equation (7) tend to overestimate the experimental values, while Equation (8) shows better predictive accuracy. This is attributed to the similar surface properties of SFCB and FRP reinforcement, as well as the similarity in bond failure mechanisms between SFCB-concrete and FRP-concrete.…”
Section: Design Recommendationsmentioning
confidence: 99%
“…However, the poor ductility and low elastic modulus of the FRP limits its direct application in structures [6]. Therefore, a new type of reinforcement material called Steel-FRP composite bars (SFCBs) [7] has emerged, which wraps FRP around a steel core [8]. Although existing studies indicate that water molecules diffuse within the FRP in the direction of the resin and fiber-resin interface in marine environments, thereby degrading the performance of the FRP [9,10], in general, FRP still exhibits better seawater corrosion resistance compared to steel reinforcement.…”
Section: Introductionmentioning
confidence: 99%